Investigation of techniques to replace amalgamation in artisanal gold mining operations - Torkaman, Pariya; Veiga, Marcello; Lavkulich, Leslie; Klein, Bern (International Journal of Sustainable Energy and Environmental Research, 2023)
Artisanal gold mining is the leading source of anthropogenic mercury emissions worldwide. This article explores cost-effective gold leaching methods for skilled miners to address mercury’s environmental and health impacts in this sector. A sample from Colombia’s La Maria deposit, containing 48.87 ppm gold, ground to 80% below 0.13 mm, served as the basis for comparison. The standard whole ore amalgamation approach, commonly used by miners, resulted in less than 19% gold extraction. However, employing cyanidation with 1g/L of free cyanide extracted 84% of the gold within 24 hours. Among the unconventional processes investigated, using effluent from a local cassava processing plant as a lixiviant demonstrated promise. Two cassava varieties produced liquids with 267 and 600 mg/L of free cyanide, leading to 50.9% and 82.4% gold extraction from the ore in 24 hours, respectively. Another alternative method involved employing Dimethyl sulfoxide, a water-free reagent, as a gold-leaching lixiviant, resulting in a remarkable 96.5% gold extraction in just 2 hours. The researchers also modified the Merrill-Crowe cyanidation process by eliminating filtration and vacuum, instead utilizing bags filled with zinc (or aluminum) in the pulp. With reduced agitation to prevent aeration, over 99% of the gold precipitated on the zinc shavings within 2 hours. Furthermore, testing a hydrochloric solution (50%) with an oxidant demonstrated 83.9% and 100% gold extraction in 8 hours at ambient temperature and 50°C, respectively. It is crucial to note that successful implementation of these alternative strategies necessitates knowledge, investment, and customization to suit specific site conditions.